Beyond Productivity Loss in Brainstorming Groups: The Evolution of a Question - Wolfgang Stroebe; Bernard A. Nijstad; Eric F. Rietzschel (Center for Research in Economics, Management and the Arts (CREMA), 2014)
Why do interactive brainstorming groups perform so much worse than individuals working as nominal groups? This was the original question, which stimulated three decades of research, as described in this chapter. Three different phases in brainstorming research can be distinguished, each of which answered a new question. In Phase 1, interactive brainstorming groups were compared with nominal groups with respect to the quantity of ideas produced, and production blocking (having to take turns to express ideas) was identified as the major cause of productivity loss. But why did production blocking have such devastating effects on idea generation? To answer this question, a cognitive model was developed and tested in Phase 2. Blocking was shown to lead to cognitive interference. But at the same time, evidence indicated that exchanging ideas could have cognitive stimulation effects. This opened the possibility that with blocking effects removed, exposure to the ideas of others could increase idea quality as well as quantity. Therefore, in Phase 3, research attention shifted to idea quality. It was found that a deep exploration of categories of ideas led to higher idea originality. To assess whether participants were able to identify their best ideas, we added idea selection to idea generation and found that people prefer ideas that are feasible to those that are original. The outcomes of each of these phases have implications for work in other areas, including group performance, human memory, and creativity. These implications, as well as the implications for practice, are discussed.
Keywords: 330